Jysk Arkæologisk Selskab i mere end 50 år - Laursen, Jesper (Kuml, 2001)
The Jutland Archaeological Society For more than fifty years The Jutland Archaeological Society was founded in 1951 (figs. 1-2). According to the objects clause, it is the purpose of the society to ”support archaeological research through the largest possible participation of all interested. It should make archaeology accessible to the public by – among other things – publishing an annual and a number of scientific publications, by having yearly meetings, excursions to larger excavations and in any other way, which the governing body sees fit.” The Jutland Archaeological Society was therefore not meant to deal just with matters concerning Jutland, and if one looks at the activities of the society during the first ten years the object was obviously more extensive. Whereas more than half of the articles in the annual Kuml dealt with the Prehistory and Middle Ages in Denmark, the second half included the related disciplines of ethnology, ethnography, philology and science, and also classical archaeology and the archaeology of the Near East – the latter because of the Danish expeditions to the countries along the Arabian Gulf. One initiative, which helped in making the society known, was the institution of the J.J.A.Worsaae Medal in 1956 as a celebration of the fifth anniversary of the society. This is a gold medal and a sum of money, which is given for special merits within Nordic archaeology. One may have a critical approach to the fact that a narrow circle of colleagues are handing nice medals to each other. However, the institution of the Worsaae Medal with its stress on ”Nordic archaeology” has increased the public understanding of the Jutland Archaeological Society as the representative of a judicious mixture of local, national, Nordic and international interests (fig. 3). Another cunning move was made in connection with the fifth anniversary, when twenty-eight leading archaeologists from seventeen European countries and the Soviet Union, the United States, and Mexico were appointed corresponding members. At the tenth anniversary this list was supplemented by another eleven highly respected foreign scholars. The reason for appointing a person as a corresponding member was ”credits within archaeological research”, and by this move the society and its activities no doubt became known in the right places. From the start, summaries in the most common foreign languages in Kuml and in the monographs (which were later to an increasing extent published in a principal language) made the publications internationally accessible. Through the ordinary members abroad, the corresponding members and – not the least – the many exchange connections to archaeological institutions abroad, this was fully accomplished. Finally, another remarkable initiative should be mentioned, which only a few would connect with the Jutland Archaeological Society. This is the archaeological newsletter, which was started by the then museum keeper Harald Andersen. The name of this periodical is ”Skalk” (old Germanic for ”servant” or ”marshal”, later terming a prankster). This periodical set a fashion for a long row of popular magazines not only in Denmark, but also in our neighbouring countries (fig. 4). After just a few years, Skalk had more than 10.000 members. The number later rose to 60.000, and in 1963, Skalk was separated from the society and became an independent enterprise under Harald Andersen’s leadership. When drawing up the balance sheet for the first ten years of the Jutland Archaeological Society, one realises that not only did the society justify its existence, it also made itself known as a shining example, not just to the members, but to the archaeological environment as such. Starting from the provincial level, within a few years it had gained national, Nordic and international status. Setting off from a concept embracing the diversity of human life, the society settled on a wide history-of-culture approach to its activities and encouraged a fruitful, mutual inspiration rather than sterile and pent-up specialist delimitation. In time Kuml developed a specialist character with many, thoroughly prepared and well-documented find presentations (fig. 5). Not only did Kuml develop into one of our best-edited archaeological journals; it also differed in design from other publications. From 1958 it had a hard cover, and since 1970 the cover has been decorated with remarkable graphic variations on a theme presented in the volume concerned. Since 1951, various scholarly volumes have been published, four in the 1950s, four in the 1960s and seven in the 1970s. However, since then the number of publications has risen dramatically, with fifteen volumes in the 1980s and twenty-five from 1990 to 2000 (see the list of Jutland Archaeological Society publications in the back of this book). The explanation to this explosive development is partly the fact that a number of large excavation projects have begun to bear fruit – as for instance the investigations in the Arabian Gulf countries, in the valley of Illerup, and in Sarup – partly the increased excavation activity of archaeological institutions and the excavation boom experienced since the 1970s. What may then be expected from the Jutland Archaeological Society in the future? Apart from offering good lectures and exciting travels to near and remote places, the society must of course live up to the decisions of its objects clause, i.e. to support archaeological research and make archaeology accessible for the public by publishing an annual and larger scholarly publications. It is a sign of the times that the books in the scholarly publication series will play a large part in the society’s future activities. The publication demand is enormous, as the museum s have been excavating more than ever over the past twenty years and there are no signs of this developm entchanging. Jesper Laursen Moesgård Museum Translated by Annette Lerche Trolle